EFFECT OF MAGNESIUM WITH ROPIVACAINE IN SUPRACLAVICULAR BRACHIAL PLEXUS BLOCK FOR POST-OPERATIVE ANALGESIA: A RANDOMIZED CONTROLLED STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Supraclavicular brachial plexus block (SCBPB) is widely used for upper limb surgeries, providing reliable anesthesia and prolonged postoperative analgesia. Ropivacaine, a long-acting amide local anesthetic, offers favorable sensory-motor differentiation with reduced cardiotoxicity. Magnesium sulfate, an N-methyl-D-aspartate (NMDA) receptor antagonist, has been increasingly evaluated as an adjuvant to enhance the quality and duration of regional blocks. Objective: To evaluate the effect of magnesium sulfate as an adjuvant to ropivacaine in ultrasound-guided supraclavicular brachial plexus block on onset, duration of block, and postoperative analgesia. Methods: In this prospective, randomized, double-blinded controlled study, 60 adult patients (ASA I–II) undergoing elective upper limb surgeries were randomly allocated into two groups. Group R (n=30) received 20 mL of 0.5% ropivacaine. Group RM (n=30) received 20 mL of 0.5% ropivacaine with 150 mg magnesium sulfate. Sensory and motor block onset times, duration of blocks, time to first rescue analgesia, Visual Analog Scale (VAS) scores, and hemodynamic parameters were recorded and analyzed. Results: The addition of magnesium significantly prolonged the duration of sensory block (812 ± 64 min vs 620 ± 58 min; p